2011
DOI: 10.1152/ajpcell.00139.2011
|View full text |Cite
|
Sign up to set email alerts
|

A calcineurin homologous protein is required for sodium-proton exchange events in the C. elegans intestine

Abstract: Caenorhabditis elegans defecation is a rhythmic behavior, composed of three sequential muscle contractions, with a 50-s periodicity. The motor program is driven by oscillatory calcium signaling in the intestine. Proton fluxes, which require sodium-proton exchangers at the apical and basolateral intestinal membranes, parallel the intestinal calcium flux. These proton shifts are critical for defecation-associated muscle contraction, nutrient uptake, and longevity. How sodium-proton exchangers are activated in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Indeed, it was recently found that loss of Caenorhabditis elegans (C. elegans) chp1 orthologous, pbo-1 (posterior body contraction mutant) function results in a weakened defecation muscle contraction and a caloric-restriction phenotype of C. elegans. Pbo-1 affects defecation in C. elegans by regulating differentially the activity of intestinal NHE exchangers located at the apical and basolateral intestinal membranes of C. elegans (149). Further studies using this and other animal models may aid identifying the global effects of losing CHP function.…”
mentioning
confidence: 99%
“…Indeed, it was recently found that loss of Caenorhabditis elegans (C. elegans) chp1 orthologous, pbo-1 (posterior body contraction mutant) function results in a weakened defecation muscle contraction and a caloric-restriction phenotype of C. elegans. Pbo-1 affects defecation in C. elegans by regulating differentially the activity of intestinal NHE exchangers located at the apical and basolateral intestinal membranes of C. elegans (149). Further studies using this and other animal models may aid identifying the global effects of losing CHP function.…”
mentioning
confidence: 99%
“…Consistent with this idea, a reduction in either nhx-2 or vha-6 expression or activity is associated with reduced fat stores and increased lifespan (Nehrke, 2003; Allman et al, 2009; Wagner et al, 2011). This is consistent with the idea that nutrient deprivation extends lifespan but that too much deprivation—such as might occur in the loss-of-function nhx-2 and vha-6 mutants—leads to starvation.…”
Section: Ph Homeostasis: Protons At Workmentioning
confidence: 68%
“…It is reasonable to propose that ingestion of pathogens triggers a shift from defecation (muscle contraction) to pathogen defense (production of H 2 O 2 ) in C. elegans. The PBO-1 and PBO-4 proteins are conserved in mammalian cells [15,16] and it will be interesting to determine whether these proteins have a similar role in regulating pH and immune function in higher species.…”
Section: Discussionmentioning
confidence: 99%
“…PBO-1 was first identified because of its contribution to the posterior body contraction (Pbo) phenotype [14]. PBO-1 is an EF-hand protein orthologous to human CHP1 (Calcineurin B homologous protein 1, also called P22) [15]. It is thought that PBO-1 links the release of intracellular calcium to the activity and/or trafficking of Na + /H + -exchangers (NHE or NHX), including NHX-2, NHX-6 and PBO-4 (also known as NHX-7) [16].…”
Section: Introductionmentioning
confidence: 99%